CHARACTERISATION OF ACACIA AND EUCALYPTUS PLANTATION WOOD FOR VENEER PRODUCTION IN VIETNAM - Hien Mai, Trinh; Redman, Adam (Journal of Forestry Science and Technology, 2018)
This study presents the characterisation of three most commercially common Vietnamese hardwood plantation Acacia mangium, Acacia hybrid (Acacia mangium × Acacia auriculiformis), Eucalyptus urophylla) for veneer production. The aim of the study was to provide the veneer processing industry with linkages between current hardwood plantation resource characteristics and utilisation potential. Research results indicated that some species appear to perform better than others in terms of peeled veneer quality dependent on the final utilisation of the veneer or veneer based products. Eucalyptus urophylla produces veneer with higher stiffness and a higher proportion of stiffer material than the other species at a similar age, may be more suitable for structural products than the other species. Net recovery, which indicates the saleable volume recovered, varied between 49% and 55%, approximately double that reported for solid wood processing (sawmilling) of similar diameter and plantation species. A very high proportion of the recovered veneer meets the requirements of D-grade in accordance with Australian and New Zealand standard AS 2269.0:2012, only a small proportion meets the requirements of higher grade qualities, with the exception of 14 and 19-year-old Eucalyptus urophylla. In addition, a grading system for peeled logs in Vietnam was proposed in this study.